KEWENANGAN MAJELIS KEHORMATAN NOTARIS DALAM MEMBERIKAN PERSETUJUAN TERHADAP PEMANGGILAN PENYIDIK PENUNTUT UMUM DAN HAKIM BERKAITAN DENGAN KETENTUAN PASAL 66 AYAT ( 1 ) UNDANG-UNDANG JABATAN NOTARIS - IWARIS HAREFA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Saidin3. Suprayitno Notarial is a credible position in doing the profession in legal service for people. It is one of the honorable and noble professions (officium nobile). As a public official, a Notary is the one who is trusted to give advice. Since Law No. 2/2014 on the Amendment of Law No. 30/2004, the Notarial Advisory Council has been established. The role and authority of this new institution replaces the role and authority of the Regional Advisory Council in giving approval of summoning a Notary by investigator, general prosecutor, and judge stipulated in Article 66, paragraph 1. The research problems are how about the guidance done by the Notarial Advisory Council according to Article 66 of the Notarial Act, how about the legal ground of the Notarial Advisory Council in giving approval of summoning by investigator, general prosecutor, and judge stipulated in Article 66 of the Notarial Act, and how about the right and obligation of a Notary after the Notarial Advisory Council has given their approval.Keywords: Notary, Article 66, Notarial Advisory Council